2021
DOI: 10.3389/fpsyg.2021.745252
|View full text |Cite
|
Sign up to set email alerts
|

How Presenteeism Shaped Teacher Burnout in Cyberbullying Among Students During the COVID-19 Pandemic

Abstract: The pandemic caused by SARS-CoV2 has had an impact on the education sector, and its stakeholders, such as teachers who had to do remote work from their home, despite many constraints. These professionals tried to perform their teaching functions, despite having to deal with adverse situations, such as cyberbullying among their students, as well as their difficulties related to presenteeism and burnout. In this context, this study aimed to understand whether observing cyberbullying among students can be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
(137 reference statements)
2
7
0
1
Order By: Relevance
“…Numerous studies have documented the negative impact of the COVID‐19 pandemic on teachers' wellbeing 16,24,25 . Our study corroborates and extends this research by demonstrating a similar pattern of self‐described poor mental health among a large sample of K‐12 teachers, and by demonstrating the association between poor mental health and considering leaving the teaching profession.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Numerous studies have documented the negative impact of the COVID‐19 pandemic on teachers' wellbeing 16,24,25 . Our study corroborates and extends this research by demonstrating a similar pattern of self‐described poor mental health among a large sample of K‐12 teachers, and by demonstrating the association between poor mental health and considering leaving the teaching profession.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous studies have documented the negative impact of the COVID-19 pandemic on teachers' wellbeing. 16,24,25 Our study corroborates and extends this research by demonstrating a similar pattern of selfdescribed poor mental health among a large sample of K-12 teachers, and by demonstrating the association between poor mental health and considering leaving the teaching profession. Given the association between work-related stress and teacher attrition, 14 we hypothesize that work-related stress during the COVID-19 pandemic has simultaneously led to poor mental health and greater attrition.…”
Section: Teacher's Mental Health and Fear Of Covid-19supporting
confidence: 85%
“…Four studies had been conducted in Japan ( 31–34 ) and 4 in United Kingdom ( 35–38 ), 3 in United States ( 39–41 ), 2 in China ( 42 , 43 ), Germany ( 44 , 45 ), and the Republic of Korea ( 46 , 47 ), and 1 in Sweden ( 16 ), Wales ( 48 ), Canada ( 22 ), Turkey ( 49 ), Lithuania ( 50 ), Portugal ( 51 ), Australia and New Zealand ( 52 ), and Belgium and the Netherlands ( 53 ). In 14 of the 25 selected articles, collection took place in 2020; 6 of the 25 were collected in 2021; and the remaining 5 were collected over months in both 2020 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that between 70.6% ( 43 ) and 26% ( 38 ) of the subjects in the included studies showed sickness presenteeism. In addition, a number of factors may have also favoured presenteeism or sickness presenteeism, such as mental health-related factors [burnout ( 34 , 45 , 49 , 51 ), stress ( 33–35 , 38 , 42 , 44 , 45 , 47 , 49 ), depression ( 46 ), fear of COVID-19 ( 49 ), no well-being ( 16 , 40 ), cyberbullying ( 51 ), sleep disturbance ( 34 ), concern about having enough food ( 41 ), social isolation ( 38 ), and no resilience ( 38 )]; individual factors [poor marital relationship ( 31 ), health status ( 42 ), being young ( 38 ), attention-deficit/hyperactivity disorder symptoms ( 32 ), workers who experienced interrupted medical care ( 33 , 40 ), low physical activity ( 38 , 50 ), sedentary behaviours ( 52 ), having children ( 41 ), having health insurance ( 41 ), and having a chronic illness ( 38 )]; factors related to the situation caused by COVID-19 [confinement ( 45 ), having symptoms of respiratory infectious disease ( 48 ), not volunteering to work on the frontline ( 47 ), impact on business operations, loss of contract, and risk of bankruptcy ( 16 )]; and factors arising from working conditions [perceived organisational support ( 49 ), direct patient care ( 39 ), work functioning or task performance impairment ( 31 , 42 , 43 , 53 ), work fatigue ( 34 , 43 ), safety climate ( 22 ), workload ( 22 ), having no one to replace them ( 48 ), geographical distribution ( 48 ), transition from in-person to online modes of working ( …”
Section: Resultsmentioning
confidence: 99%
“…In this context, determining the relationship of presenteeism with social, cultural, and individual variables and revealing the results of this experience will contribute to the literature. In particular, it can be said that some cultural codes (e.g., the perception of work as worship, the sanctity attributed to services such as education, and the dominance of social control mechanisms) will help to understand the sociological and psychological elements underlying the presenteeism experience (Cooper & Lu, 2016;Ferreira et al, 2021). For this purpose, the phenomenon of presenteeism is examined according to the participants' perceptions, using a phenomenological design to analyse the phenomenological interviews, memoing, and messages received from the participants after the interviews.…”
mentioning
confidence: 99%